When Threats Come from Within: National Identity, Cascading Frames, and the U.S. War in Afghanistan. (October 2015) - Rowling, Charles M.; Gilmore, Jason; Sheets, Penelope
Scholars have widely demonstrated that the process by which officials frame their communications significantly impacts how citizens understand, evaluate, and respond to policy issues or events. This study attempts to build on existing framing research in two important ways. First, we seek to illuminate the importance of "cultural resonance" in determining whether an individual frame is likely to gain acceptance among its intended audience. Second, we assess the impact of "frame contestation" on the adoption of such frames. We explore these dynamics in the context of the U.S. war in Afghanistan. Specifically, we conducted an experiment in which U.S. adults were exposed to a news story about U.S. military transgressions in Afghanistan. Our results indicate that frames, designed to appeal to and protect the national identity, broadly resonated among respondents, impacting their perceptions of the character, causes and consequences of the transgressions, as well as their broader attitudes about the nation, the U.S. military, and the war in Afghanistan. Nonetheless, when these frames were presented, and then explicitly contested within the same news story, it diminished—but not entirely—these framing effects. We reflect on the theoretical and practical implications of these findings for journalists, officials, and the broader public.